2018
DOI: 10.18805/ijar.b-3624
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early postoperative rehabilitation with physiotherapy in the cranial cruciate ligament ruptured dogs stabilized with extra capsular technique

Abstract: The aim of the study was to find out the efficacy of rehabilitative techniques postoperatively of extracapsular stabilized cranial cruciate ligament deficiency dogs. Twelve dogs were treated surgically by extracapsular imbrication method. Post operatively six dogs were rehabilitated with neuromuscular electrical stimulation and different therapeutic exercise. The lameness score and weight score and girth of thigh differ significantly between them. Range of motion and girth also improved but non significantly. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The percentage distribution of the identified 18 muscle function assessment methods among all the included studies ( n = 139) and studies focusing on CCLD [ n = 16 ( 1 , 6 , 14 , 34 , 35 , 39 , 40 , 45 – 53 )] are shown in Figure 3 . Ten out of the 18 muscle function assessment methods were applied in studies on CCLD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The percentage distribution of the identified 18 muscle function assessment methods among all the included studies ( n = 139) and studies focusing on CCLD [ n = 16 ( 1 , 6 , 14 , 34 , 35 , 39 , 40 , 45 – 53 )] are shown in Figure 3 . Ten out of the 18 muscle function assessment methods were applied in studies on CCLD.…”
Section: Resultsmentioning
confidence: 99%
“…Video analysis without markers, accelerometry/pedometry, and ultrasound were some of the methods that were not applied among the CCLD studies. Scoring systems were applied in five of the CCLD studies and covered simple lameness scores but with different scales ( 6 , 34 , 35 , 39 , 40 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrotherapy is also used in veterinary medicine in order to treat acute and chronic pain in patients with orthopaedic and neurologic signs. Alternating currents of low frequency are usually used in veterinary medicine, like NMES (Neuromuscular Electrical Stimulation) and TENS (Transcutaneous Electrical Nerve Stimulation) (Hussain et al, 2019;Dumitrescu and Cristina, 2015;Samoy et al, 2016).…”
Section: Introductionmentioning
confidence: 99%